The Arabidopsis Protein CONSERVED ONLY IN THE GREEN LINEAGE160 Promotes the Assembly of the Membranous Part of the Chloroplast ATP Synthase. Issue 1 (24th March 2014) - Rühle, Thilo; Razeghi, Jafar Angouri; Vamvaka, Evgenia; Viola, Stefania; Gandini, Chiara; Kleine, Tatjana; Schünemann, Danja; Barbato, Roberto; Jahns, Peter; Leister, Dario
Abstract : A thylakoid membrane protein promotes the assembly of the protein complex that generates ATP in chloroplasts . Abstract: The chloroplast F1 Fo -ATP synthase/ATPase (cpATPase ) couples ATP synthesis to the light-driven electrochemical proton gradient. The cpATPase is a multiprotein complex and consists of a membrane-spanning protein channel (comprising subunit types a, b, b′, and c) and a peripheral domain (subunits α, β, γ, δ, and ε). We report the characterization of the Arabidopsis ( Arabidopsis thaliana ) CONSERVED ONLY IN THE GREEN LINEAGE160 (AtCGL160) protein (AtCGL160), conserved in green algae and plants. AtCGL160 is an integral thylakoid protein, and its carboxyl-terminal portion is distantly related to prokaryotic ATP SYNTHASE PROTEIN1 (Atp1/UncI) proteins that are thought to function in ATP synthase assembly. Plants without AtCGL160 display an increase in xanthophyll cycle activity and energy-dependent nonphotochemical quenching. These photosynthetic perturbations can be attributed to a severe reduction in cpATPase levels that result in increased acidification of the thylakoid lumen. AtCGL160 is not an integral cpATPase component but is specifically required for the efficient incorporation of the c-subunit into the cpATPase . AtCGL160, as well as a chimeric protein containing the amino-terminal part of AtCGL160 and Synechocystis sp. PCC6803 Atp1, physically interact with the c-subunit. We conclude that AtCGL160 and Atp1 facilitate the assembly of the membranous part of the cpATPase in their hosts, but loss of their functions provokes a unique compensatory response in each organism.